2013
DOI: 10.7733/jkrws.2013.11.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination Reaction Behavior of Zircaloy-4 Hulls: A Preliminary Study on the Effect of the Oxidation Process on the Reaction Rate

Abstract: The recovery of Zr from Zircaloy-4 (Zry-4) cladding hulls was demonstrated to investigate the effect of the oxidation process on the reaction rate of the chlorination reaction. In chlorination reaction experiments performed for 6 h, where reaction products were collected every 2 h, it was observed that a significant decrease in the reaction rate was caused by the oxidation process (500 o C, 10 h under an air atmosphere) within the reaction period of 0 -2 h. The amount of reaction residue increased from 0.95 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, the chlorination reaction result of ZIRLO-500-24 (35.3% weight loss) shows that the chlorination reaction can proceed in the absence of ZrO when the thickness of the oxide layer is thin enough (about 3.22 μm). A gap in the reactivity between side walls and cutting edges should be considered, because the XPS results represent the oxidation status of side walls while the chlorination reaction prefers cutting edges [15]. The photograph of ZIRLO-500-24 shown in ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, the chlorination reaction result of ZIRLO-500-24 (35.3% weight loss) shows that the chlorination reaction can proceed in the absence of ZrO when the thickness of the oxide layer is thin enough (about 3.22 μm). A gap in the reactivity between side walls and cutting edges should be considered, because the XPS results represent the oxidation status of side walls while the chlorination reaction prefers cutting edges [15]. The photograph of ZIRLO-500-24 shown in ref.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, the next work should be done for oxidized cladding hulls, because actual cladding hulls have micrometers thick oxide layers on their side walls. It was qualitatively identified that oxidized cladding hulls suffer from incubation time [5] or late reaction rate in an early stage of the chlorination reaction [7]. A quantitative analysis on the effect of oxide layer formation can be identified using the TGA-HC system, and the results will contribute to the design of a large scale cladding hull chlorination system.…”
Section: Zirlo Versus Zircaloy-4mentioning
confidence: 99%
“…At KAERI, fundamental approaches including reaction kinetics were mainly made to build a database for scale-up [7e9]. The first approaches were done using a quartz reactor by repeated experiments for various reaction periods [7]. In that study, a linear reaction rate equation was achieved for bare Zircaloy-4 cladding hulls, while delayed reaction rate was observed in oxidized Zircaloy-4 cladding hulls.…”
Section: Introductionmentioning
confidence: 99%